Lumbar spine stability following hemilaminectomy, pediculectomy, and fenestration - Hill, T. P.; Lubbe, A. M.; Guthrie, A. J. (Veterinary and Comparative Orthopaedics and Traumatology, 2000)
The destabilising effect of the removal of a single vertebral diarthrosis and the ipsilateral incision of the anuliis fibrosus at two adjacent vertebrae in the canine lumbar spine was quantified in an in vitro study. Lumbar spine segments, from the first to fourth lumbar vertebrae, were harvested from canine cadavers and divided into 1 control group (A) and 3 experimental groups - hemilaminectomy and fenestration (B), pediculectomy and fenestration (C), fenestration alone (D). Samples were subjected to 4 point lateral bending to point of failure. Stiffness, maximum bending moment (Mbmax), angular deformation and bending moment at 15° (Mb at 15°) variables were determined for each group. Hemilaminectomy and fenestration had the greatest decrease in Mbmax, Mb at 15° and stiffness and the greatest increase in angular deformation. Pediculectomy and fenestration and the fenestration alone procedures caused similar and significant reductions in Mb at 15° and stiffness. Pediculectomy was less destabilizing than hemilaminectomy, although this difference was not statistically significant. Fenestration is the common and greatest destabilizing factor. The removal of a single pedicle and accessory process has minimal destabilizing effects.The destabilizing effect of hemilaminectomy, pediculectomy and fenestration were quantified and compared in a study using canine cadaver spines. The combination of hemilaminectomy and fenestration produced the greatest degree of instability, but fenestration was the shared, most significant, single destabilizing factor.
Keywords: Pediculectomy; spine; biomechanics; stability; canine